2022
DOI: 10.1128/jvi.01831-21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Capsid Maturation Facilitates the Resolution of Conflicting Requirements for Herpesvirus Assembly

Abstract: Most viruses undergo a maturation process from a weakly self-assembled, noninfectious particle to a stable, infectious virion. For herpesviruses, this maturation process resolves several conflicting requirements: i) assembly must be driven by weak, reversible interactions between viral particle subunits to reduce errors and minimize energy of self-assembly; ii) the viral particle must be stable enough to withstand tens of atmospheres of DNA pressure resulting from its strong confinement in the capsid. With her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…pUL17 is important for genome packaging and the efficient recruitment of pUL25 and pUL36 to capsids [12,14]. pUL25 on capsid vertices prevents the capsid structure from rupturing after packaging [17,18]. Further, recent cryo-EM studies examining pUL25 and its β-and γ-herpesvirus homologs have demonstrated that pUL25 adjacent to the capsid portal is thought to extend over the portal, forming a pentameric portal cap that plugs the capsid portal after genome packaging [14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…pUL17 is important for genome packaging and the efficient recruitment of pUL25 and pUL36 to capsids [12,14]. pUL25 on capsid vertices prevents the capsid structure from rupturing after packaging [17,18]. Further, recent cryo-EM studies examining pUL25 and its β-and γ-herpesvirus homologs have demonstrated that pUL25 adjacent to the capsid portal is thought to extend over the portal, forming a pentameric portal cap that plugs the capsid portal after genome packaging [14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…pUL17 is important for genome packaging and the efficient recruitment of pUL25 and pUL36 to capsids (12, 14). pUL25 on capsid vertices prevents the capsid structure from rupturing after packaging (17, 18). Further, pUL25 adjacent to the capsid portal is thought to extend over the portal, thereby plugging it after genome packaging (14).…”
Section: Introductionmentioning
confidence: 99%